Reference in selected articles of Dr. Ibrahim Al Turki’s book " Wafq al- tawqīt al- ʻArabī" - Al-Sohebani, Norah Abdullah; Al- Atta, Amal Othman (Arab Journal for Sciences and Research Publishing, 2019)
The present paper tackles the impact of grammatical reference on the shaping of the textual structure in terms of fulfilling its grammatical coherence and semantic relationships. The researcher has taken three essays from Ibrahim Al Turki’s book " Wafq al- tawqīt al- ʻArabī ": "Paradox, Balance, and Transformation." The paper has relied on a modern linguistic theoretical framework, known as text linguistics. An analytical descriptive approach has been used by the Researcher to highlight and analyze types of references contained in the corpus being studied from a grammatical and semantic perspective in a manner related to the content and purposes of the author. The study, in general, has reached significant results, which can be summed up into the interplay of grammatical reference and the construction of the text, with an emphasis on ensuring its grammatical cohesion and semantic coherence. In addition, it plays a role in the conciseness of language and conveys the stances of the text author in relation to its theme, through linguistic and grammatical devices to express difference, paradox, agreement, transgression and other relations.